A Clinical Study of Photodynamic Therapy for Superficial Esophageal Carcinoma by YAG-OPO Laser. Issue 4 (1998) - Yoshida, Kazunari; Suzuki, Shigeru; Mimura, Seishiro; Narahara, Hiroyuki; Tanimura, Hiroshi; Nagai, Yugo; Isono, Kaichi; Kozu, Teruo; Fukutomi, Hisayuki; Nakahara, Akira; Kashimura, Hiromasa; Hirashima, Toshio; et al.
Abstract : A cooperative clinical study of photodynamic therapy (PDT) for superficial esophageal carcinoma was conducted at 6 medical institution. PHE (2mg/kg) with high tumor affinity was used as the oncotropic compound. The light source was a pulse wave YAG-OPO laser with high penetration into the tissue. Irradiation was performed at an energy density of 60–180 J/cm 2 48–72 h after PHE administration. Eight lesions in 6 patients were treated. All were type 0-II superficial carcinomas. The depth of invasion was EP–MM for 6 lesions and SM for 2 lesions. A complete response (CR) was achieved in all patients after one session of PDT. Five adverse events, including anemia and fever, were reported by 4 patients, but all were WHO grade 2 or lower and transient. PDT using PHE and YAG-OPO laser was therefore considered effective as a curative therapy for superficial esophageal carcinoma.